The assessment of routine health information system performance towards improvement of quality of reproductive, maternal, newborn, child and adolescent health services in Ondo and Ekiti States, Nigeria - Victoria Oladoyin; Sunday Adedini; Kayode Ijadunola; Hassan Ogunwemimo; Olubunmi Folorunso; Elizabeth Chukwu; Ugo Okoli; Anthony Adoghe; Samuel Oyeniyi; Oniyire Adetiloye; Adesegun Fatusi (PLoS ONE, 2025)
Background Nigeria’s reproductive, maternal, newborn, child, and adolescent health indicators have remained unsatisfactory in the face of poor-quality healthcare services. Nigeria initiated the reproductive, maternal, newborn, child, and adolescent, elderly + nutrition (RMNCAEH+N) quality of care (QoC) agenda to address the challenge. The health management information system (HMIS) is integral to the agenda but there is sparse evidence on its performance so far. This study assessed the performance of routine HMIS for RMNCAEH+N QoC in Ondo and Ekiti States. Methods This paper described the review of health facility records and health facility survey components of a multi-component study which employed a mixed-method research design. Using the routine health information system performance diagnostic tool, service data captured for over one year were critically reviewed in randomly selected sample of 169 public health facilities (Ondo:117; Ekiti:52) and information was obtained from facility heads or designates. Performance of routine HMIS for RMNCAEH+N QoC in terms of data collection, data quality, and data use were analysed using univariate and bivariate statistics. Results Results show that 67.3% of health facilities in Ekiti and 88.9% of facilities in Ondo had all required HMIS tools for selected RMNCAEH+N services (p<0.001). Data accuracy was 70.1% for Ondo and 40.4% for Ekiti (p <0.001); 82.9% of facilities in Ondo and 44.2% in Ekiti had complete data (p <0.001); almost all facilities (Ondo: 99.1%; Ekiti: 96.2%, p = 0.224) demonstrated data consistency; and, 82.9% of facilities in Ondo and 94.2% of facilities in Ekiti demonstrated timeliness in data submission (p = 0.048). Also, 70.1% (Ondo) and 78% (Ekiti) of facilities had quality improvement (QI) teams (p = 0.338); 53.5% (Ondo) and 77.1% (Ekiti) of QI teams regularly extracted data, calculated, and visualised prioritized indicators (p = 0.007); while 72.1% (Ondo) and 79.2% (Ekiti) regularly reviewed data and used it to make QI decisions (p = 0.367). Conclusion Routine RMNCAEH+N QoC data management system in Ondo and Ekiti States vary in terms of the status of reporting forms, data quality, and data use for decision-making, and there were specific performance gaps. The routine RMNCAEH+N QoC data management system in Ondo and Ekiti States needs improvement and findings from this study can serve as the basis for evidence-based advocacy for the required efforts and investment toward improved performance.